Cross-disc coupling in a flexible shaft–disc assembly in presence of asymmetric axial–radial bearing supports. (9th June 2022) - Tuzzi, G.; Schwingshackl, C.W.; Green, J.S.
Abstract: In a flexible shaft–disc assembly supported by linear bearings, the disc 1 Nodal Diameter (ND) modes are known to couple with the shaft lateral (bending) modes, whilst the 0ND modes can couple with the shaft axial modes. In addition to these well known coupling phenomena, a previous work by the authors has shown that, in presence of an asymmetric axial–radial bearing supporting structure, shaft axial and lateral modes can interact and lead to a coupling with a single flexible disc 0 and 1 ND modes simultaneously. Given that in most circumstances a shaft carries more than one disc, this work extends the previous findings to a shaft carrying two flexible discs and particularly investigates the mechanisms of cross disc coupling due to an asymmetric supporting structure. A full 3D FEM model of the assembly has been developed to model its dynamic behaviour. New classes of coupled modes involving the shaft and the two discs have been identified and a physical explanation will be provided, considering forces/moments applied at the interface amongst subcomponents and following the hypothesis that each disc acts like an independent dynamic absorber. A parametric study of the dual discs arrangement varying stiffness, thickness and position of one disc further highlighted the dynamic interaction of the subcomponents. Specific arrangements will allow an Engine Order forcing pattern applied to one disc to excite a different mode on the other disc, with the shaft and the supports acting as the vibration energy transmitter between the two discs. The industrial implications of such phenomena are also discussed throughout this work.